JUSTICE AND LEGAL CERTAINTY FOR LAND TITLE HOLDERS IN THE PROCUREMENT OF LAND FOR PUBLIC PURPOSES - Basri, Hasan (Jurnal IUS, 2013)
The land acquisition process for public interest in many case donât work properly. It usually causedby the reluctance of land ownership right holders to release their land. Generally because theyfelt their rights were unprotected especially the right to get proper compensation. This researchaimed to find out and to understand about legal protection to the land ownership right holdersin land acquisition for public interest and its implementation by studied case of land acquisitionfor PLTU (steam power plant) development in west Lombok . This research used a normativeâsociological research method which focus on the ârealization and implementationâ of normativelegal (in abstracto) in certain legal case (in concerto) or in other phrase methods of this researchmeant to see how legal works in the society. Research result shown that land ownership rightholders in land acquisition for PLTU development in west Lombok did not get optimum legalprotection which caused by unserious attention from the regulation of land acquisition for publicinterest to this matter. Beside that, the official of land acquisition for public interest did not gavetheir maximum effort to protect related rights and the reluctance of land ownership right holdersto registered their land also causing lack protection of their rights.Keywords: Legal Protection, Land Acquisition